2022
DOI: 10.1002/jat.4390
|View full text |Cite
|
Sign up to set email alerts
|

Potential issues specific to cytotoxicity tests of cellulose nanofibrils

Abstract: Cellulose nanofibrils (also called cellulose nanofibers or nanofibrillated cellulose [CNFs]) are novel polymers derived from biomass with excellent physicochemical properties and various potential applications. However, the introduction of such new materials into the market requires thorough safety studies to be conducted. Recently, toxicity testing using cultured cells has attracted attention as a safety assessment that does not rely on experimental animals. This article reviews recent information regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 66 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…It should be noted that the cytotoxicity of novel materials at the nanoscale based on natural biopolymers strongly depends on the source, isolation protocol, functionalization, dimensions and studied cell line. , Thus, a direct comparison between different nanomaterials is difficult due to the lack of well-established protocols. Some review papers have tried to summarize those recent studies dealing with the cytotoxicity of cellulose-based nanomaterials, which share structural and chemical similarities to the ChNFs presented herein. , Hanif et al prepared cellulose nanocrystals of controlled shape and size and studied their potential cytotoxicity with murine fibroblasts (NIH3T3) . The prepared CNCs did not have any detrimental effect on cell viability at concentrations of up to 250 μg·mL –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the cytotoxicity of novel materials at the nanoscale based on natural biopolymers strongly depends on the source, isolation protocol, functionalization, dimensions and studied cell line. , Thus, a direct comparison between different nanomaterials is difficult due to the lack of well-established protocols. Some review papers have tried to summarize those recent studies dealing with the cytotoxicity of cellulose-based nanomaterials, which share structural and chemical similarities to the ChNFs presented herein. , Hanif et al prepared cellulose nanocrystals of controlled shape and size and studied their potential cytotoxicity with murine fibroblasts (NIH3T3) . The prepared CNCs did not have any detrimental effect on cell viability at concentrations of up to 250 μg·mL –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Some review papers have tried to summarize those recent studies dealing with the cytotoxicity of cellulose-based nanomaterials, which share structural and chemical similarities to the ChNFs presented herein. 54 , 55 Hanif et al prepared cellulose nanocrystals of controlled shape and size and studied their potential cytotoxicity with murine fibroblasts (NIH3T3). 28 The prepared CNCs did not have any detrimental effect on cell viability at concentrations of up to 250 μg·mL –1 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In discussing the safety of CNFs, Nadia et al [19] reported that endotoxin (lipopolysaccharide, LPS) is a component of the cell wall of Gram-negative bacteria and is responsible for various pathological conditions in bacterial infections. Moriyama et al [20] described the presence of endotoxin in CNFs. Menas et al [21] used the Pierce LAL Chromogenic Endotoxin Quantitation Kit (Thermo Fisher Scientific, Waltham, MA, USA) to measure endotoxin contamination in five different nanocellulose materials, including lyophilized CNF powder.…”
Section: Discussionmentioning
confidence: 99%
“…The results revealed an elevation in the levels of these cytokines in response to the presence of unmodified CNFs. Notably, the proinflammatory impact was not found in the cells when they were subjected to treatment with modified CNFs (214). The utilization of a crosslinking agent, namely polyethyleneimine, along with a surfactant called cetyltrimethylammonium bromide, for the purpose of modifying CNFs, led to a noteworthy diminution in both the viability and proliferation of fibroblast cells as compared to the unmodified CNFs in their pure form (215).…”
Section: Cellulosementioning
confidence: 98%